The impact Sino-Zimbabwe bilateral diplomatic relations on economic and political development from 2008-2016 - Guse, Chipo Mellisa (Midlands State University, 2018)
The bilateral diplomatic relations of Zimbabwe and China re surfaced in a crucial time of economic and international politics hardship for Zimbabwe. This has caused too much expectation from the Zimbabweans and serious bargain allegations on China from these relations. This has led to a number of people including the international arena questioning the relevance or rather importance of these bilateral relations. Therefore, the focus of the study is on the impact of bilateral diplomatic relations between China and Zimbabwe from 2008 to 2016. The problem surrounding these relations include misunderstanding by the public on what really the relationship nature is like, most people would take it as China trying to aiding Zimbabwe when in actual fact the relations are designed to mutually benefit both parties business wise, the damage that China is trying to heal on Zimbabwe is kind of underrated and also the media exaggerates what really the relations are yielding positively or negatively. A literature/document review was done to find what other scholars say concerning the relations between China and Zimbabwe with the aim of identifying some literature gaps and areas that need contribution. Other countries like Uganda, Nigeria and South Africa were observed to have the same bilateral relations with China though their results are not entirely identical to those of Zimbabwe. The objective of the study is to find what inspired the Sino-Zimbabwe relations, the rationale of the relations, to analyse the development that has taken place and assessing the impact of the relations with the aim of proffering some recommendations. To satisfy the objectives, focus group discussions from the ordinary citizens on whom the impact of the relations reflects vividly was conducted and questionnaires distributed. The respondents raised issues such as corruption, monopolisation of deals, lack of grass root support to be the reasons for negative impact the Sino-Zimbabwe relations have. Much appreciation was to the positive impact where the respondents acknowledged how even the poorest of the people can afford life through cheaper goods, how these relations have blocked further sanctions to be imposed and foreign direct investment from China is somehow sustaining the economy. The researcher then concluded that bilateral relations can impact more positively given that the government of Zimbabwe amends its economic and political development policies as well as manage the funds efficiently. Recommendations prior to the improvement of how the relations are done were given and these were: involvement of the ordinary citizens in developmental policy making because they know exactly what happens on the ground so that the relations gain grass root support, to have public reports on financial audit especially for the loans and investment from these relations for the sake of transparency, policy review and adjustments and effectively dealing with corruption so as to assure the public that compliance with law is also their main concern. The research paper is in five chapters which are: chapter one Introduction (background of the study, justification of the study, statement of the problem, limitation and delimitations, chapter two Literature review and other country experience, chapter three Methodology (methods of data collection), chapter four Presentation and analysis of findings and chapter five Conclusion and recommendations.